The Relationship between Mother-in-Law Characteristics and Postpartum Bleeding Events at Afisya Clinic, Dusun III, Melur Sambirejo East, Deli Serdang Regency, 2018-2022 - Supriati; Rina Marlina Hutasuhut (PT Inovasi Pratama Internasional, 2022)
According to a report from the World Health Organization, maternal deaths generally occur due to complications during and after pregnancy and childbirth. Globally 80% of maternal deaths are classified as direct deaths. The pattern of direct cause was the same everywhere, namely bleeding (25%). It is said that every woman dies every minute during childbirth, where 24% is caused by heavy bleeding. 40% of deaths due to postpartum hemorrhage occur in the first 24 hours and 66% occur during the first week. The aim is to determine the relationship between the characteristics of mothers in labor and the incidence of postpartum hemorrhage at the Afisya Clinic. This type of research is Analytical Survey with a cross-sectional design. Population 118 and sample 118, Data processing: editing, coding, tabulating, and data entry. The results of the study showed that the majority of primary postpartum hemorrhage was 78 people and a minority of secondary postpartum hemorrhage was 40 people. The age majority is at risk of 79 people and the minority is not at risk of 39 people. The parity majority is at risk of 74 people and the parity minority is not at risk of 44 people. The majority of birth spacing has a risk of 79 people and the minority delivery spacing is not at risk of 39 people. From the results of statistical tests, the Oods Ratio (OR) = 0.321% CI = 0.126-0.817 and the value is 0.0250.005, which means that there is no relationship between education and postpartum hemorrhage. From the statistical test results, the Oods Ratio (OR) value = 0.308% CI = 0.126-0.754 and P Value 0.014 which means there is a relationship between postpartum hemorrhage parity.